Assessing the Quality of Life of Children’s with Acute Respiratory Tract Infections - Dhamotharan, Jothieswari; Dinesh Kumar, Durga Prasad; Rajasekaran, Lakshmi Raj Sulochana; Mondal, Vinnayak; Selvan, Rachana Panner; Shaik, Shaik Arshad Mohammad; Roshni, Ravi; Bhargavi, Thanakanti (Journal of Pharmacy Practice and Community Medicine)
Background: Acute Respiratory Tract Infections (ARTIs) are one of the most commonly occurring diseases. Importantly, ARTIs are the most prevalent disease among children, especially for 2 to 6 year old children. ARTIs are often related to genetic factors, lower immune functioning, vitamin and mineral deficiencies, improper feeding and nursing, residential environment and other variables. Aim: This research aimed to provide scientific insight into ways to address and improve health related quality of life in children with ARTIs and their caregivers. Objective: To observe the quality of life with acute respiratory infection and to minimize the acute respiratory infections. Methods: A prospective cross sectional study was conducted on 200 patients, majority of the subjects belongs to the age group of 0.3 to 4years on contrast, least number of subjects were observed between the ranges of 5 to 11 years. Results: ARTIs found insignificant relationship between the social history and disease outcome. 18.5% of the subject parents found to be smokers. On a deeper analysis of smoking pattern and behavior among the parents, we found great impact of such attitude contributing to acute respiratory tract infection. Results of the study reveal that 81% of cases were reported in excellent score. Conclusion: Most of the parents were aware and they did not smoke near child. So this factor not involved effectively in child to get respiratory tract infection. We noticed partial correlation coefficient in case of parental smoking. This suggested us that parental smoking had very less impact on quality of life of patients with ARTIs.
Keywords: Acute respiratory tract infections (ARTIs); Quality of Life; Children; Pneumonia; Asthma.